Host-seeking activity of a Tanzanian population of Anopheles arabiensis at an insecticide treated bed net - Josephine E. A. Parker; Natalia C. Angarita Jaimes; Katherine Gleave; Fabian Mashauri; Mayumi Abe; Jackline Martine; Catherine E. Towers; David Towers; Philip J. McCall (Malaria Journal, 2017)
Abstract Background Understanding how mosquitoes respond to long lasting insecticide treated nets (LLINs) is fundamental to sustaining the effectiveness of this essential control tool. We report on studies with a tracking system to investigate behaviour of wild anophelines at an LLIN, in an experimental hut at a rural site in Mwanza, Tanzania. Methods Groups of adult female mosquitoes (n = 10 per replicate) reared from larvae of a local population, identified as predominantly (95%) Anopheles arabiensis, were released in the hut. An infrared video tracking system recorded flight and net contact activity over 1 h as the mosquitoes attempted to reach a supine human volunteer within a bed net (either a deltamethrin-treated LLIN or an untreated control net). A range of activities, including flight path, position in relation to the bed net and duration of net contact, were quantified and compared between treatments. Results The total time that female An. arabiensis spent in flight around LLINs was significantly lower than at untreated nets [F(1,10) = 9.26, p = 0.012], primarily due to a substantial reduction in the time mosquitoes spent in persistent ‘bouncing’ flight [F(1,10) = 18.48, p = 0.002]. Most activity occurred at the net roof but significantly less so with LLINs (56.8% of total) than untreated nets [85.0%; Χ2 (15) = 234.69, p < 0.001]. Activity levels at the bed net directly above the host torso were significantly higher with untreated nets (74.2%) than LLINs [38.4%; Χ2 (15) = 33.54, p = 0.004]. ‘Visiting’ and ‘bouncing’ rates were highest above the volunteer’s chest in untreated nets (39.9 and 50.4%, respectively) and LLINs [29.9 and 42.4%; Χ2 (13) = 89.91, p < 0.001; Χ2 (9) = 45.73, p < 0.001]. Highest resting rates were above the torso in untreated nets [77%; Χ2 (9) = 63.12, p < 0.001], but in LLINs only 33.2% of resting occurred here [Χ2 (9) = 27.59, p = 0.001], with resting times spread between the short vertical side of the net adjacent to the volunteer’s head (21.8%) and feet (16.2%). ...